Relationship between Self-Control and Bullying Incidents in Adolescents At SMPN 29 Batam - Laska, Yulinda; Maulani, Rici Gusti; Nurlela, Siti (Bunda Edu-Midwifery Journal (BEMJ), 2024)
Background: Adolescents are synonymous with turbulent emotions but have imperfect self-control. Recently, cases of loss of self-control have occurred in adolescents due to lack of self-control. Low self-control leads to adolescent involvement in aggressive actions such as bullying. The aim of this research is to determine the relationship between self-control and bullying incidents in adolescents at SMPN 29 Batam. Methods: This research uses quantitative research methods with analytical correlation research with a cross sectional approach. The sampling technique used probability sampling (simple random sampling) with a total of 87 respondents. The research instrument used was a questionnaire. Data analysis used the chi square statistical test. Result: From this research, the results obtained from 87 respondents were that most teenagers who had low self-control carried out bullying and acted as perpetrators of bullying, namely 43 people (91.5%), while 1 teenager who had high self-control carried out bullying ( 2.5%). Chi square test results with p value 0.000 less than 0.05. Conclusions: It can be concluded that there is a significant relationship between self-control and the incidence of bullying in adolescents at SMPN 29 Batam. The suggestions in this research are expected for adolescents to be able to add information about how to increase self-control and for educational institutions to provide education about self-control to adolescents as a form of education to increase self-control in adolescents and prevent bullying.